Morally injurious events among aid workers: examining the indirect effect of negative cognitions and self-care in associations with mental health indicators - Dewar, Michelle; Paradis, Alison; Brillon, Pascale (Frontiers in Psychology, 2023)
Introduction Potentially morally injurious events (PMIE) are events that violate one’s deeply held moral values or beliefs, and that have the potential to create significant inner conflict and psychological distress. PMIE have been recognized as an important psychological risk factor in many high-risk occupational groups. However, no study to date has investigated how PMIE relate to the mental health of aid workers. Furthermore, little is known about the mechanisms by which PMIE might be associated with mental health indicators. Methods Participants were 243 aid workers (72% female; Mage = 39.31) who had completed at least one aid assignment (M = 8.17). They completed an online questionnaire about their PMIE, trauma history, and mental health. A structural equation model was constructed to examine the roles of negative cognitions and subsequent self-care behaviors in the relationship between PMIE and PTSD symptoms, depression symptoms, and posttraumatic growth, above and beyond the contribution of potentially traumatic events. Results Within the model, the indirect effect through negative cognitions fully accounted for the associations between PMIE and symptoms of PTSD and depression. For the association between PMIE and posttraumatic growth, two indirect effects emerged: the first through negative cognitions and subsequent self-care and, the second, through self-care alone. Discussion This study highlighted PMIE as a novel psychological risk factor for aid workers and pointed to two possible mechanisms by which these events may lead to PTSD, depression, and posttraumatic growth. This study adds to the current understanding of how high-risk occupational groups adapt psychologically to PMIE.